Visual Outcome Mapping of Learning Connections and Interventions for Higher Education - Dhaarna; Komal Handore (The Indonesian Institute of Science and Technology Research, 2026)
Modern higher education is under siege, and various difficult issues have emerged as a result of changing students' needs and diverse learning styles. These include problems associated with curriculum design, student retention, quality of teaching and learning processes, and integration of technology. The modern technological tool named Visual Outcome Mapping (VOM) has evolved and has the potential to provide innovative solutions by acquiring, analyzing, and presenting data relevant to student performance in pursuit of effective personalized learning and timely feedback. The mapping is done between challenges, teaching methodologies, and levels of Bloom’s Taxonomy using VOM. The paper highlights that even small engagement and creative activities can lead to achieving higher-order skills. It elaborates how the usage of creative tools like GIS and Mentimeter leads to enhanced engagement, while real-life scenario integration, breakpoint activities, site visits, hands-on assignments, and continuous feedback have shown positive impacts on critical thinking and reduced instances of plagiarism. It focuses on teaching strategies that must be adapted to student needs and interdisciplinary learning must be emphasized. The VOM model was validated with the analysis of 108 survey samples collected from the students as feedback using the correlation technique. It concludes that students learn better with activities and they prepare students for the demands of the real world. VOM is a creative approach that addresses the challenges of modern education, ensuring that students are well-prepared for the workforce and committed to lifelong learning. The study paves the way for future research and scope.